Museums: risks and stripes - França Lourenço, Maria Cecília (Revista ARA, 2018)
The arts in general constitute practices with wide duration and, although they can connect to power, sometimes dark and unspeakable indeterminacies unfold, in particular, to join the creation and institution critical to time function created. Without reducing the fetish, the pair to join requires reviewing boundaries, borders, rules laid down by dogma, rhetoric, prejudice, apparent brightness and dictated by media spectacle. A long, domain and wealthy social classes add personal image with art collected, then open to the public at various times and regions. Nevertheless, State policy in places like Argentina and Portugal come faced historical past and dark deeds for public initiatives. The domain of such agents in broad spectrum, some to keep and others to turn, it would be Ethereal, or means only new coalitions at the top. In this configuration between opposing forces will endure sensitive systems, museums and creators as defined today?